2008
DOI: 10.1590/s0102-37722008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Habilidades sociais na agorafobia e fobia social

Abstract: RESUMO -Os transtornos ansiosos são freqüentemente associados ao défi cit de habilidades sociais (HS). A fobia social é o quadro mais relacionado a esse défi cit, enquanto a agorafobia é desconsiderada. O objetivo deste artigo é investigar essa associação por meio de uma revisão da literatura. Foi realizada uma busca eletrônica nas bases de dados PsycINFO, MEDLINE e SCIELO, além das referências dos trabalhos selecionados. O défi cit de HS mostrou-se mais presente nos estudos que avaliaram o desempenho de indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
(21 reference statements)
1
2
0
6
Order By: Relevance
“…It is considered that the mental health problems in university students may also favor problems in social functioning, emotional and school problems (Isolan et al, 2007), and increased stress (Fernandes & Land, 2008), which, in a certain way, restricts the possibilities for development in this crucial time for the adult, professional, and personal roles. It was verified that the literature is inconclusive regarding the relationship between anxiety and social skills, with some authors having reported such a relationship (Angélico et al, 2006) and others not (Levitan et al, 2008), which is the insertion context of this study. The results identified in this study indicate a relationship between these variables, as the clinical group was less skilled than the non-clinical group, considering the two instruments that assess social skills, endorsing the assertions made by Angélico et al (2006).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It is considered that the mental health problems in university students may also favor problems in social functioning, emotional and school problems (Isolan et al, 2007), and increased stress (Fernandes & Land, 2008), which, in a certain way, restricts the possibilities for development in this crucial time for the adult, professional, and personal roles. It was verified that the literature is inconclusive regarding the relationship between anxiety and social skills, with some authors having reported such a relationship (Angélico et al, 2006) and others not (Levitan et al, 2008), which is the insertion context of this study. The results identified in this study indicate a relationship between these variables, as the clinical group was less skilled than the non-clinical group, considering the two instruments that assess social skills, endorsing the assertions made by Angélico et al (2006).…”
Section: Discussionsupporting
confidence: 70%
“…However, they warned that further studies needed to be conducted with clinical and non-clinical samples using precise diagnostic criteria, in order to support the association between social skills and social phobia. Conversely, Levitan, Rangé, and Nardi (2008), also based on a literature review, reported that only some of the studies reviewed found that social skills deficits were related to social anxiety and indicated gaps in the knowledge related to social skills.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uma condição associada a esses dados é uma sensibilidade à ansiedade, ou seja, o medo da sensação de ansiedade originado pela crença de que esta pode trazer consequências prejudiciais. Essa condição aparece fortemente associada a formas desadaptativas de processamento emocional e regulação do afeto, como uso de estratégias de evitação 20 , aspecto associado a déficits em habilidades sociais 21 .…”
Section: Introductionunclassified
“…O primeiro trabalha com diversos transtornos de ansiedade, transtorno do pânico (Rangé, 2001), fobia social (Levitan et al, 2008) e demais transtornos de ansiedade, como fobias específicas. O segundo trabalha de forma mais específica com o transtorno obsessivo-compulsivo, tendo desenvolvido manuais de terapia para esse transtorno assim como protocolos para terapia de grupo (Cordioli, 2014).…”
Section: Introductionunclassified